In Vitro Evaluation of Oxidative Stress Biomarkers in the Muscle Tissue of Rainbow Trout (Oncorhynchus mykiss Walbaum) Exposed To Leaf Extract of Ficus benjamina L. and ITS Cultivars - Buyun, Lyudmyla; Tkachenko, Halyna; Maryniuk, Myroslava; Kharchenko, Igor; Osadowski, Zbigniew; Honcharenko, Vitaliy; Prokopiv, Andriy (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
The aim of this study was to evaluate the in vitro effect of extracts obtained from leaves of Ficus benjamina L. and its cultivars on the oxidative stress biomarkers (carbonyl content of the oxidatively modified proteins, total antioxidant capacity) in the muscle tissue of the rainbow trout. The leaves of F. benjamina and its cultivars, i.e. F. benjamina ’Safari’, ’Baroque’, ’Amstel Gold’, ’Reginald’ were sampled for our study. Our results showed that extracts obtained from leaves of F. benjamina ’Safari’ and F. benjamina ’Reginald’ decreased non-significantly the lipid peroxidation biomarker in the muscle tissue. Extracts obtained from leaves of F. benjamina and its cultivars decreased the ketonic derivatives of oxidatively modified proteins in the muscle tissue. Our results showed that extracts obtained from leaves of F. benjamina and its cultivars increased efficiently the total antioxidant capacity in muscle tissue by 76.9 % (F. benjamina), 66.9 % (F. benjamina ’Safari’), 70.5 % (F. benjamina ’Baroque’), 49.4 % (F. benjamina ’Amstel Gold’), and 42.8 % (F. benjamina ’Reginald’) (p<0.05). The results of this study provide a new perspective on the use of various Ficus species as a medicinal plant to improve the antioxidant response of rainbow trout. Further studies including the use of other medicinal plants as food additives in aquaculture, the assessment of their antioxidant effects on various tissues of salmonids are in progress.